Crystalline lens changes after selective laser trabeculoplasty in Afro‐Caribbean patients with open‐angle glaucoma; report 4 of the West Indies Glaucoma Laser Study (WIGLS). Issue 10 (October 2019) - Realini, Tony; Shillingford‐Ricketts, Hazel; Burt, Darra; Balasubramani, Goundappa K.
Abstract : Purpose : To characterize changes in nuclear, cortical, and posterior subcapsular lens opacities after selective laser trabeculoplasty (SLT) in Afro‐Caribbean eyes with primary open‐angle glaucoma (POAG). Setting : Three clinical practices, Saint Lucia and Dominica. Design : Prospective case series. Methods : Patients with POAG in the West Indies Glaucoma Laser Study (WIGLS) had 360‐degree SLT after medication washout. No antiinflammatory therapy was used after SLT. Nuclear, cortical, and posterior subcapsular lens opacities were graded through dilated pupils using the Lens Opacification Classification System III (LOCS III) at baseline and 12, 24, and 36 months after SLT, with the grader masked to all previous values after baseline assessment. Changes in opacity scores from baseline were evaluated using paired t tests. Results : Seventy‐two patients (142 phakic eyes) were evaluated. The mean (±SD) baseline LOCS III opacity scores in right eyes and left eyes, respectively, were 2.44 ± 1.23 and 2.40 ± 1.16 (nuclear), 0.39 ± 1.08 and 0.30 ± 0.85 (cortical), and 0.22 ± 0.59 and 0.15 ± 0.36 (posterior subcapsular). Other than a small improvement in bilateral nuclear opacity scores at 12 months, no statistically or clinically significant changes in any opacity score occurred in either eye up to 36 months postoperatively. Three eyes (2.1%) with preexisting lens opacities had cataract surgery for progressive lens changes at 3 months, 21 months, and 26 months, respectively, after SLT. Conclusions : Selective laser trabeculoplasty was not associated with clinically significant changes in nuclear, cortical, or posterior subcapsular lens opacities in glaucomatous Afro‐Caribbean eyes. The rate of cataract surgery is consistent with reported rates from longitudinal natural history studies in Caribbean and non‐Caribbean populations.